2009
DOI: 10.1186/1746-6148-5-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of cultural methods for the detection of Salmonella in feed and feed ingredients

Abstract: Background: Animal feed as a source of infection to food producing animals is much debated. In order to increase our present knowledge about possible feed transmission it is important to know that the present isolation methods for Salmonella are reliable also for feed materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
3
16
0
1
Order By: Relevance
“…While the EFSA reported that the prevalence of Salmonella in other feed raw materials, e.g., grain, was significantly lower (6), Koyuncu and Haggblom observed that the sensitivity of cultural detection methods varied with the type of ingredient tested (30). Data collected here with PCR-based methods confirm the observations of Koyuncu and Haggblom (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…While the EFSA reported that the prevalence of Salmonella in other feed raw materials, e.g., grain, was significantly lower (6), Koyuncu and Haggblom observed that the sensitivity of cultural detection methods varied with the type of ingredient tested (30). Data collected here with PCR-based methods confirm the observations of Koyuncu and Haggblom (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, data from the various serotypes were pooled. In an earlier study using culture-based detection methods, we observed that even though feed ingredients were spiked with identical Salmonella cell numbers, detection limits varied with ingredient type (30). Similar results were obtained when PCR-based methods were employed in this study.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Isolation and identification of Salmonella: Culture and isolation of Salmonella was conducted using standard method ISO 6579 as previously described [11]. Transparent well-isolated colonies with black center typical Salmonella morphology were collected from selective media and identified by using biochemical reactions.…”
Section: Samplesmentioning
confidence: 99%
“…The same methods are principally also applied in the food industry and on samples from different environmental as well as clinical sources. Modified semisolid rappaport vassiliadis (MSRV)-based methods have been shown to be suitable for testing of feed [22]. An official authorization also of their use for feed and foodstuffs as well as for samples from primary food animal production would offer significant benefits in terms of harmonization across the food chain.…”
Section: Methods For Detecting and Sub-typingmentioning
confidence: 99%